PENGARUH PROMOSI, KUALITAS PELAYANAN JASA DAN CITRA TERHADAP PENGAMBILAN KEPUTUSAN MAHASISWA UNIVERSITAS NEGERI JAKARTA - Suliyanthini, Dewi (Parameter, 2015)
This causal research aims to assess the direct of the promotion, service quality, and image toward the decision making student at the universitas State of Jakarta. The data where collected from a randomly selected sampel of 383 student University State of Jakarta. The research was implemented during five months from August until October 2010. The questionnaire was signed by Likert sale. A path analysis technique was employed to analyse the data descriptively and inferentially. The research finding show that (1) a direct effect of the promotion toward the image, (2) a direct effect of the service quality toward the image, (3) a direct effect of the promotion toward the decision making, (4) a direct effect service quality toward the decision making, (5) a direct effect image toward the decision making. These finding suggest that the promotion, Service quality, and image were determining factors toward the decision making student at the University State of Jakarta, hence the research need to take into consideration for developing of University of Jakarta.